2020
DOI: 10.1080/20964129.2020.1715264
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing perennial and indeterminant growth habits for ratoon cotton ( Gossypium spp.) cropping

Abstract: Ratoon is the stub or root of a perennial plant that is commonly retained after harvest to produce a following crop. This paper presents a review of ratoon cotton in relation to a broader framework that has been examining perennialization of agriculture for the benefit of ecology and economy. Cotton is botanically indeterminate, but has been treated as an annual after domestication, yet the habit of perenniality is retained and the plants begin to resprout after the first harvest. In some cropping systems, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…The annual cotton cultivars were domesticated from perennial species in tropical and subtropical regions (Huang and Hao, 2018;Jadhav and Bhosale, 2018). However, the annual cultivated species still have perennial habits [i.e., ratooning ability (RA) which mainly refers to the ability of the ratoon crops to maintain cotton yield and fiber quality of the previous growth cycle], which can be utilized for perennial ratooning in tropical or subtropical regions, although the stalks should be pruned before the subsequent season (Zhang et al, 2020). Some studies have shown that the annual species can be ratoon cultivated for approximately 3 years while still producing high yields (Fontes et al, 2006;Zhang et al, 2015a).…”
Section: Ratoon Cotton Culturementioning
confidence: 99%
See 4 more Smart Citations
“…The annual cotton cultivars were domesticated from perennial species in tropical and subtropical regions (Huang and Hao, 2018;Jadhav and Bhosale, 2018). However, the annual cultivated species still have perennial habits [i.e., ratooning ability (RA) which mainly refers to the ability of the ratoon crops to maintain cotton yield and fiber quality of the previous growth cycle], which can be utilized for perennial ratooning in tropical or subtropical regions, although the stalks should be pruned before the subsequent season (Zhang et al, 2020). Some studies have shown that the annual species can be ratoon cultivated for approximately 3 years while still producing high yields (Fontes et al, 2006;Zhang et al, 2015a).…”
Section: Ratoon Cotton Culturementioning
confidence: 99%
“…However, there can be problems associated with ratooned annual cotton, such as: (1) multiple ratooning, which facilitates the accumulation of overwintering pests and diseases ( Plucknett et al, 1970 ; O’Brien, 2016 ) and leads to reductions in boll size ( Macharia, 2013 ; Zhang et al, 2015a ), and (2) susceptibility to an abnormal climate during winter, which has two different effects – stand loss during severe winters ( Sachs and Zilkah, 1985 ; Zhang et al, 2008 ) and harmful regrowth during mild winters ( Greenberg et al, 2007 ; O’Brien, 2016 ). In addition, the dramatic increase in labor costs requires implementation of a mechanized one-off cotton harvest, which is difficult to achieve in ratooned annual cotton with a long boll-opening period ( Zhang et al, 2020 ).…”
Section: Benefits and Problems Associated With Ratooned Annual Cottonmentioning
confidence: 99%
See 3 more Smart Citations